Simbol Kekuasaan Ilahi dan Keruntuhan Arogansi: Analisis Semiotika Roland Barthes terhadap Surat al-Fil. - Yudistira, Saptanadi; Muliadi, Muliadi; Taufiq, Wildan (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
This research aims to analyze the layered meanings in Surat al-Fil using Roland Barthes' semiotic approach, particularly to reveal the denotative and connotative meanings of the main symbols in the surah. This study employs a qualitative-descriptive method with a text analysis approach. Primary data is derived from the text of Surat al-Fil, while secondary data consists of scholarly references related to semiotics and Qur’anic exegesis. The results of the study show that symbols such as Tairan Ababil, Hijaaratin min sijjil, and Ka’asfin Ma’kul not only describe the historical events of the destruction of the elephant army (denotative meaning) but also contain a mythological narrative about divine intervention against forms of worldly arrogance. The novelty of this research lies in the integration of Barthes' theory in interpreting Surat al-Fil as a symbolic discourse of resistance against ideological domination and tyrannical power. Implicitly, this approach opens up space for critical-ideological contemporary interpretations in understanding divine messages and can serve as a narrative basis for shaping social awareness and public policy based on divine values.